In vitro and skin lesion cytokine profile in Brazilian patients with borderline tuberculoid and borderline lepromatous leprosy - Venturini, James [UNESP]; Soares, Cléverson Teixeira; Belone, Andréa de Faria Fernandes; Barreto, Jaison Antonio; Ura, Somei; Lauris, José Roberto Pereira; Vilani-Moreno, Fátima Regina (My University, 2011)
Objective: We investigated the in vitro and skin lesions production of cytokines in non-treated borderline tuberculoid (BT) and borderline lepromatous (BL) patients. Patients and Methods: Seven untreated, non-reactional BT patients and 12 untreated, non-reactional BL patients were studied. Levels of the cytokines IFN-γ, IL-10, TGF-β1 and TNF-α were measured in supernantant of peripheral blood mononuclear cells (PBMC) cultures, stimulated with specific M. leprae antigen (sonicated and whole). The cytokines iNOS, IL-10 and TGF-β1 were detected by immunohistochemistry in skin biopsies. Results: BT patients produced higher levels of IFN-γ than BL patients; iNOS expression in skin lesions was also higher in BT patients. TGF-β1 was detected in more cells in BL patients; IL-10 expression was similar in both groups. There was a negative correlation between iNOS and TGF-β1 expression in skin biopsies, positive correlation between TGF-b1 in skin lesions and bacillary index, as well as positive correlation between iNOS detected in skin biopsies and PBMC IFN- γ production. Conclusions: The BT patients had a mainly a Th1-profile of cytokines in their skin lesions and BL patients had aTh2 profile. © Lepra.